How to maintain environmental integrity when using state support and the VCM to co-finance BECCS projects - a Swedish case study - Dufour, Malin; Möllersten, Kenneth; Zetterberg, Lars (Frontiers in Environmental Science, 2024)
Limiting global warming to close to 1.5 °C by 2100 requires deep and rapid greenhouse gas (GHG) emission reductions and carbon dioxide removals (CDR) on a massive scale, presenting a remarkable scaling challenge. This paper focuses on the financing of bioenergy with carbon capture and storage (BECCS) in Sweden. BECCS is one of the most prominent CDR methods in 1.5 °C-compatible global emission scenarios and has been assigned a specific role in Swedish policy for net-zero. A Swedish state support system for BECCS based on results-based payments is planned. Furthermore, demand for CDR-based carbon credits is on the rise on the voluntary carbon markets (VCM) for use towards voluntary mitigation targets. Risks involved with the current Swedish policies are analysed, specifically for the co-financing of BECCS by the planned state support and revenues from the VCM. We find that with the current policies, state support systems will subsidise carbon credit prices on the VCM. We argue that such subsidisation can lower decarbonisation efforts by lowering the internal carbon price (ICP) set by actors, thus undermining environmental integrity. It is concluded that proportional attribution should be applied, i.e., attributing mitigation outcomes to the state support and VCM revenue in proportion to their financial contribution to the CDR achieved. The attribution analysis should be accompanied by adjustments in national greenhouse gasGHG accounting so that mitigation outcomes that are issued as carbon credits and used for offsetting are not double claimed (i.e., not used by both a nation and a non-state actor on the VCM towards their respective mitigation targets). If proportional attribution and adjustments in national GHG accounting are not implemented, the credibility and environmental integrity of offsetting claims made by carbon credit users are eroded. We recommend that action is taken to operationalise and implement proportional attribution to allow for co-financing of BECCS projects while maintaining environmental integrity. Wider implications for our recommendations beyond the case of Swedish BECCS are also analysed.